Effects of extracellular K+ on grapevine membrane potential as influenced by the antiviral mycophenolic acid. An electrophysiological study - Andrea Luvisi; Enrico Rinaldelli; A. Panattoni (Advances in Horticultural Science, 2015)
Mycophenolic acid (MPA) is an effective antiviral drug in plants, and its action in modulating the activity of KATP channels is already known in animals. In the present work, an electrophysiological study was carried out to investigate MPA effects on plant K+ channels, through the measurement of trans-plasma membrane potential in samples of Vitis vinifera cv. Sangiovese treated with extracellular K+. Tests confirmed that the administration of MPA (in preincubated samples or in those maintained under chemical treatment) can reduce the membrane depolarization induced by K+. However, MPA-induced alteration in membrane potential was sensitive to the KATP channel opener diazoxide, as well to treatments with guanosine. This result confirms the effectiveness of MPA in influencing KATP channel activity as well as inhibiting activity of the inward-rectifier potassium ion channel which could be mediated by guanosine depletion induced by MPA.